PENGARUH LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS TERHADAP PERUBAHAN LABA PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI TAHUN 2013 – 2017 - Yuigananda, Amalia; Rachmawati Dewi, Riana; Masitoh, Endang (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
Financial ratio analysis is used to asses management performance in achieving targets (profits) that have been set in management capabilities and empowering company resources effectively. This study aims to determine the effect of Current Ratio, Total Dept To Total Asset, Dept To Equity Ratio, Gross Profit Margin, Net Profit Margin to changes in earnings. This research is a descriptive study, with a population of 18 Food and Beverage companies listed on the Indonesia Stock Exchange in 2013 – 2017. The sampling technique was purposive sampling, the sample in this study were 7 Food and Beverage companies listed on the Indonesia Stock Exchange in 2013 – 2017. The results of this study are from five independent variables, namely the current ratio, total dept to total assets, dept to equity ratio, gross profit margin, only two variables that influence changes in earnings, namely current ratios with results of tcount (-1,716) > ttable ( 1,699) and gross profit margin with the results of tcount (-2,520 > ttable (1,669), the remainder is the total dept variable to total assets, dept to equity ratio, net profit margin does not affect earnings changes.